Manajemen Pembelajaran dalam Meningkatkan Pendidikan Karakter Guna Mewujudkan Generasi Emas Indonesia Siswa MTS Tahfidz Yanbu’ul Qur’an Kudus, Indonesia - Yogik Delta Hermawan (DAYAH: Journal of Islamic Education, 2021)
This study aims to determine how learning management can improve student character education to realize Indonesia's golden generation in MTs Tahfidz Yanbu'ul Qur'an Kudus, Indonesia. This study uses a qualitative approach, which describes the phenomena and facts in the field. Data collection techniques used were observation, interviews, and documentation. Data analysis is carried out through three techniques: data reduction, data display, and conclusion or verification of data. This research shows that the implementation of learning management focuses on four elements, namely curriculum management, human resource management, facilities and infrastructure management, and assessment management. Learning management can improve character education for students. Students' attitudes, including religious activities, discipline, responsibility, hard work, and social care, can be seen. Of the five components, of course, can have a positive impact in order to realize Indonesia's golden generation in the future. The supporting factors of the implementation of learning management above are adequate human resources, very supportive facilities and infrastructure, and consistency in the implementation of learning management. At the same time, the inhibiting factors are the lack of teaching staff and the density of student activities.